Uji Stabilitas Fisik dan Kimia Sediaan Tablet Parasetamol dalam Berbagai Kondisi Penyimpanan - M. Jian Prayoga; Maulida Maulida; Maura Putri Ariqah; Nor Latifah (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Paracetamol is a widely used analgesic and antipyretic drug in tablet dosage form. Ensuring the stability of paracetamol tablets is essential to maintain drug efficacy, safety, and quality during their shelf life. This study aims to evaluate the physical and chemical stability of paracetamol tablets stored under different temperature and humidity conditions. The review method used in this article involves analyzing published data from several sources, focusing on changes in physical appearance (color, shape, and odor) and chemical parameters such as active pharmaceutical ingredient content over time. The findings indicate that higher temperatures and humidity accelerate degradation and affect the drug's quality, particularly through discoloration and reduction in active content. Packaging also plays a crucial role in maintaining stability, especially in tropical climates. The results highlight the importance of stability testing in pharmaceutical quality assurance and support the application of Good Manufacturing Practices (GMP) and appropriate storage guidelines. This paper contributes to the understanding of stability profiles of commonly used drugs and provides a reference for the formulation and packaging development of heat-sensitive medications.